Environmental Issues and Reflection of their Perception in Internet Media - Dasa Novacikova (Communications - Scientific letters of the University of Zilina, 2017)
The purpose of this study is to determine the extent to which the media are devoted to global environmental problems and to how they measure them. The initial categorization of the published texts in reputable online media with national coverage (that also has its printed counterpart), specifies how and where the most important environmental issues are reflected in online media, more specifically in SME and Pravda. We believe that only marginal space is dedicated to the important environmental issues. The basis of the content analysis is to document the frequency and the thematic focus of the contributions dedicated to environmental topics. Within this study attempts are made to highlight the media‘s ability to positively influence and shape public opinion. It also aims to emphasize the importance of the media’s educational character in the context of environmental themes, the publishing of which has global importance.